2011
DOI: 10.1093/aob/mcr157
|View full text |Cite
|
Sign up to set email alerts
|

Sporophytic self-incompatibility genes and mating system variation in Arabis alpina

Abstract: The results strongly suggest that, as with other species in the Brassicaceae, A. alpina has a sporophytic SI system but shows variation in the strength of SI within and between populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 110 publications
8
85
0
Order By: Relevance
“…The 200 bp sequences produced similar resolution in phylogenetic clustering as previous studies using 600 bp (Tedder et al, 2011) and resulted in consistent patterns of polymorphism expected for dominant and recessive alleles at SRK. Examination of relative frequency distributions also generally met theoretical expectations but indicated no obvious differences in diversity between ploidy levels.…”
Section: Objectives 1 and 2: Diversity And Allele Sharing Of Srk In Dsupporting
confidence: 63%
See 2 more Smart Citations
“…The 200 bp sequences produced similar resolution in phylogenetic clustering as previous studies using 600 bp (Tedder et al, 2011) and resulted in consistent patterns of polymorphism expected for dominant and recessive alleles at SRK. Examination of relative frequency distributions also generally met theoretical expectations but indicated no obvious differences in diversity between ploidy levels.…”
Section: Objectives 1 and 2: Diversity And Allele Sharing Of Srk In Dsupporting
confidence: 63%
“…Other alleles predicted to be unlinked to the SI phenotype were also resolved by the clustering analysis but none of these would have been assigned as SRK-like based on BLAST (Table 6; Supplementary Table 10). One published allele (AlySRK32) whose phylogenetic position and dominance have not been resolved in previous studies was pulled out from six accessions; based on the length of its branch to other SRK sequences, it has been predicted to be unlinked to the SI phenotype (Tedder et al, 2011). AlySRK47 (found in four of the accessions) is also predicted to be unlinked, based on its phylogenetic position relative to linked sequences.…”
Section: Objective 4: Copy Number Variation In the Srk-related Gene Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Bars ¼ 10 mm. siliques containing seed (Mable et al, 2005;Bechsgaard et al, 2006;Tedder et al, 2011). In Brassica oleracea, instead of 20 to 25 seeds per pod produced in compatible pollinations, manual self-pollination of selfincompatible stigmas produces, on average, 0.15 to 0.25 seeds per pod (Nasrallah and Wallace, 1968;Nakanishi and Hinata, 1975) or as much as one to two seeds per pod (Thompson and Taylor, 1971 We previously reported that SRKb-SCRb transformants of the Col-0 accession produce amounts of seed equivalent to those produced by untransformed plants (Nasrallah et al, 2002(Nasrallah et al, , 2004Tantikanjana et al, 2009;Tantikanjana and Nasrallah, 2012), and this phenotype was observed in the Indriolo et al (2014) study.…”
Section: Robust Si In Srkb-scrb Transformants Of the Sha Accession Inmentioning
confidence: 99%
“…Some (inconclusive) empirical evidence for this was found in S. carolinense, where three out of five alleles without a strong genetic load were part of a clade that exhibits strong diversification, and one out of two alleles with a strong load was positioned on a long terminal branch (Stone, 2004). In sporophytic systems, relationships among S-alleles normally have low bootstrap support (Prigoda et al, 2005;Tedder et al, 2011). Moreover, comprehensive sampling of alleles is difficult (for example, Mable et al, 2003) which may compromise robust interpretation of diversification patterns (for example if close relatives of some alleles have not been sampled).…”
Section: Genetic Load Attributable To the S-locusmentioning
confidence: 99%